Kenya’s County Climate Change Fund enables communities to invest both in climate-change adaptation and peace - Pacillo, Grazia; Gadeberg, Marianne; Medina Santa Cruz, Leonardo; Schapendonk, Frans (2025)
Kenya’s County Climate Change Fund (CCCF) enables communities to prioritize, design, and secure funding for locally led climate-adaptation projects. It is operationalized by the Adaptation Consortium (ADA). In contributing to the CGIAR Research Initiative on Climate Resilience (ClimBeR), researchers from the Alliance of Bioversity International and CIAT partnered with ADA to assess how the CCCF can also address climate-related conflicts and promote peace. Based on ClimBeR’s recommendations, ADA is planning to integrate conflict prevention and resolution as an additional goal of the CCCF.